Ultra-fast all-optical switching based on nanoantenna coupled to monolayer TMDs - Song, Qige (Nanyang Technological University, 2023)
Transition Metal Dichalcogenides (TMDs) have shown great potential for applications in areas such as light capture, photodetection, phototransistors, light emitting diodes and nanolasers due to their excellent optoelectronic properties. They are currently one of the frontiers of research. The band gaps of few-layer TMDs are in the visible and near-infrared regions, and their excitons have considerable binding energies at room temperature, high resonant oscillator strengths, and valley-selective circular dichroism due to spatial inversion symmetry breaking, which make TMDs particularly attractive. These properties make the TMDs attractive. The surface plasmon polaritons of metal nanostructures have subwavelength properties, and their resonant wavelength, spectral width, near-field enhancement multiplier and far-field radiation properties can be flexibly controlled through rational structural design. The combination of the plasmon polaritons optical structure and TMDs can significantly broaden the fundamental research on the frontier of nanophotonics and the design and application of nanophotonic devices.